Exclusive breastfeeding practices reported by mothers and the introduction of additional liquids - Alessandra Marcuz de Souza Campos; Camila de Oliveira Chaoul; Elenice Valentim Carmona; Rosângela Higa; Ianê Nogueira do Vale (Universidade de São Paulo, 2015)
Aim: To assess the concept of exclusive breastfeeding held by nursing women by comparing the period they consider that they perform it and the infants' age at the introduction of additional liquids. METHOD: Cross-sectional descriptive study conducted with 309 women who delivered babies at a university hospital in the interior of São Paulo, Brazil. The data were subjected to descriptive analysis; the variables of interest were crossed using the non-parametric Kruskal-Wallis test, the chi-square test and Fisher's exact test. RESULTS: Approximately 30% of the women reported having introduced additional liquids before the infants reached aged six months old, while asserting that they were performing exclusive breastfeeding. The following variables were associated with early introduction of liquids: lack of employment (p = 0.0386), younger maternal age (p = 0.0159) and first pregnancy (p = 0.003). CONCLUSION: The concept of exclusive breastfeeding might not be fully clear to women, as they seem to believe that it means not to feed the children other types of milk but that giving other liquids is allowed. These results show that promotion of breastfeeding should take beliefs and values into consideration to achieve effective dialogue and understanding with mothers.